ANALYSIS OF THE INFLUENCE OF WORKLOAD AND WORK ACHIEVEMENT ON EMPLOYEE PRODUCTIVITY THROUGH INCENTIVE APPRECIATION AT THE NUTRITION FULFILLMENT SERVICE UNITS IN CENTRAL MAMUJU REGENCY - Andi Meity Ts Idaman Anshar; Mashur Razak; Muh. Ashary Anshar (Yayasan Education and Social Center, 2026)
This study aims to analyze the effect of workload and work performance on employee productivity through incentive appreciation at the Nutrition Fulfillment Service Unit (SPPG) in Central Mamuju Regency. The study used a quantitative approach with a survey method. The study population consisted of 119 employees, all of whom were sampled using a saturated sampling technique. Data collection was carried out through distributing questionnaires with a Likert scale, while data analysis used Structural Equation Modeling–Partial Least Squares (SEM-PLS) assisted by SmartPLS 4. The results of the study indicate that workload has a positive and significant effect on employee productivity. Work performance also has a positive and significant effect on employee productivity. In addition, workload and work performance are proven to have a positive and significant effect on incentive appreciation. Incentive appreciation further has a positive and significant effect on employee productivity. The results of the mediation analysis show that incentive appreciation partially mediates the effect of workload and work performance on employee productivity. The findings of this study indicate that employee productivity is influenced not only by workload size and high work performance, but is also strengthened by a fair, objective, and performance-based incentive appreciation system. Therefore, proportional workload management, improving work performance, and implementing a transparent incentive system are important strategies in increasing employee productivity and supporting the effectiveness of nutritional fulfillment services in Central Mamuju Regency.